(untitled) (Journal of the College of Basic Education, 2022)
There are huge benefits that offered by e-government, which can increase the number of users with big platform for transparency, as in this time the use of information technology promises to revolutionize both the provision of government services and the vibrancy of democracy. One of the solutions in many developing and developed countries is electronic voting system (E-voting) which can eliminate the needs for subjective recounts, fast and reliable delivery services, with big possibility to prevent such kind of fraud, or manipulate in results during the delivering process. The aim of this paper is to find the factors that involved in applying E-voting systems in Iraq. Overall, the paper can reveal facts for Iraqi government about adopt an electronic voting system as a replacement for the paper-based system to perform voting electoral operation efficiently and effectively.